FULFILLMENT OF RESTITUTION RIGHTS TO VICTIMS OF TRAFFICKING OFFENSES - Andi Boby Pratama R. (Transpublika Publisher, 2024)
Crime is a significant issue in Indonesia, with human trafficking being a major concern. The crime is based on Article 28, paragraph (2) of the Republic of Indonesia Constitution of 1945, which states that human rights are inalienable. The original regulation for the crime was in Article 297, which outlined the punishment for trafficking women and men who are not yet adults. However, the current rules do not provide clear protection for victims, and offenders do not face commensurate penalties. The Criminal Code provides compensation through a judge's decree, but implementation is challenging due to limitations in determining compensation and the lack of specialized legal protection for victims. This study uses normative legal research to analyze Indonesia's legal protection and compensation for victims of human trafficking, utilizing current legal materials and written works. The Criminal Code and PTPPO Law provide limited protection for victims of human trafficking, but they lack comprehensive restitution. Indonesia only approves two restitution requests, demonstrating the fundamental right to recompense. The process is lengthy and lacks evidence of expenditure, leading to uncertainty in court decisions.